Parting ways : the crisis in German-American relations - Szabo, Stephen F. (Book collections on Project MUSE., 2004)
"The first comprehensive examination of the German-American relationship written since the invasion of Iraq, Parting Ways is indispensable for those seeking to chart the future course of the transatlantic alliance." "Drawing on extensive research and personal interviews with decisionmakers and informed observers in both the United States and Germany, Stephen F. Szabo frames the clash between Gerhard Schroder and George W. Bush over U.S. policy in Iraq in the context of the larger changes shaping the relationship between the two countries. Szabo considers such longer-term factors as the decreasing strategic importance of the U.S.-German relationship for each nation in the post-cold war era, the emergence of a new German identity within Germany itself, and a U.S. foreign policy led by what is arguably the most ideological administration of the post-World War II era."--Jacket.